Reaktualisasi Pendidikan Islam - Muhammad Rusdi (Al-Riwayah : Jurnal Kependidikan, 2017)
Islamic education as an integral part of national education will give an active role and ensure the realization of national education. The goal is to complete Indonesian human development and the development of the entire Indonesian people. Renewal of Islamic education is an absolute thing to do as a way of refreshment and renewal of Islamic values in the life. This means Islamic education today is facing numerous challenges in various dimensions of life: social, economic, cultural, political, science and technology, and so on. Where are these challenges, both quantitatively will be growing up in the future. In other words, that the various demands of Muslims are facing today requires a response that is steady and concrete, among others with the ability to optimally prepare human resources Muslim reliable, independent and professional in their respective fields.